Analysis of polarisation mode splitting characteristic in optical race‐track resonator based on silicon‐on‐insulator rib waveguide. (1st October 2013) - Wei, Liping; Zang, Junbin; Wang, Yonghua; Cui, Danfeng; Li, Yanna; Liu, Yaoying; Xue, Chenyang
Abstract : The detailed design and analysis of a polarisation mode splitting resonator based on a silicon‐on‐insulator rib waveguide are presented. By analysing the mode birefringence in the ultra‐small rib waveguide, the directional coupler is introduced to the microring resonator to realise the splitting of the quasi‐TE and quasi‐TM polarisation modes from the same output port for a specific wavelength range. It is demonstrated that after splitting the quasi‐TM polarisation mode, the Q ‐value of the quasi‐TE polarisation mode is about 2.3 × 10 4, almost twice of that without splitting the quasi‐TM polarisation mode. This novel characteristic of a race‐track resonator allows it to obtain single polarisation mode at a specific wavelength by itself. This characteristic makes a contribution to accurate wavelength selection, which has been proved to be very useful in the dynamic testing of electrooptical modulators and quite promising in many other applications of optical components.